CRITICISM, INNOVATION, AND ADAPTATION OF GOVERNANCE: FROM CLASSIC TO NEW PUBLIC AND DIGITAL AMID GLOBAL CHALLENGES - Syukri; Taufiqurokhman; Satispi, Evi; Andriansyah; Muhammad Gusti (Moestopo International Review on Social, Humanities, and Sciences, 2025)
This study examines significant developments in the field of governance, tracing its transition from a classical paradigm dominated by hierarchical structures and rigid bureaucracy to a more dynamic and responsive model. Amidst the complexity of global challenges such as economic uncertainty, environmental crises, and technological disruptions, traditional governance approaches are often sharply criticized for their limitations in providing adaptive and sustainable solutions. This abstract analyzes how criticism of the classical model has become a catalyst for innovation, driving the adoption of New Public Governance (NPG), which emphasizes partnerships, multi-actor networks, and the creation of shared public value. In addition, this study explores the transformative role of Digital Governance in revolutionizing the way governments interact with citizens and provide services, increasing efficiency, transparency, and inclusion through the use of information and communication technology. With a focus on innovation and adaptation, this article aims to understand how governance systems strive to remain relevant and effective amid an ever-changing global landscape. This analysis not only highlights the historical and conceptual journey but also provides crucial insights into the need for a flexible, collaborative, and future-oriented governance framework to address the multidimensional challenges of the 21st century.